Mapping Evidence of Pharmacy Services for COVID-19 in China - Yi, Zhan-Miao; Hu, Yang; Wang, Guan-Ru; Zhao, Rong-Sheng (Frontiers in Pharmacology, 2020)
Objective To explore the role of pharmacists and innovation of pharmacy interventions for COVID-19 patients in China. Methods We comprehensively searched PubMed and Chinese databases Sinomed, China National Knowledge Infrastructure to identify articles reporting pharmacist interventions and pharmacy services for COVID-19 patients using a predefined search strategy. The search period was from inception to April 7th 2020. We also manually searched the reference list of included articles and websites of important journals with special issues for COVID-19. Results A total of 156 articles were identified by applying the search criteria. After screening, 91 articles, with the majority are literature reviews (n = 77, 84.62%) published in Chinese (n = 83, 91.2%), were included. Pharmacist interventions for COVID-19 patients most commonly related to guidelines or consensus development for the treatment of disease and practice procedure to prevent the spread of COVID-19 (n = 10, 10.98%), the supply of medicines to treat patients with severe respiratory or systematic symptoms related to COVID-19 (n = 10, 10.98%), formulating infections prevention and control strategies related to COVID-19 for pharmaceutical personnel/pharmacy staff (n = 14, 15.39%), new way of delivery pharmacy services and the implementation of new pharmacy services for COVID-19 outbreak (n = 14, 15.39%), routine pharmacy services under the restrict limit of COVID-19 outbreak (n = 39, 42.86%), and case series analysis of treatment regimens using existing, routinely collected data (n = 4, 4.40%). Conclusion Pharmacy services have a role in the COVID-19 pandemic control, and there were many rapid changes in response to the pandemic.